Analisis Kompetensi Individu dan Keadilan Organisasional Terhadap Kepuasan Kerja dan Kinerja Pegawai (Studi Empiris Kantor BPKAD Provinsi Papua Barat) - Mawirampakel, Febrilian; D. Resi, Yohanes (UNES Law Review, 2024)
This research aims to analyze the influence of individual competence and organizational justice on job satisfaction and employee performance. Data collection is through distributing questionnaires. The research sample was 48 people, using a saturated sampling technique. Meanwhile, this research uses path analysis and descriptive analysis. The research results show that: 1) Individual competency and Organizational Justice have a positive and significant effect on job satisfaction; 2) Individual competency and Organizational Justice have a positive and significant effect on employee performance; 3) Job satisfaction has a positive and significant effect on employee performance. 4) Job satisfaction is able to mediate the influence of individual competence on employee performance. 5) Satisfaction is not able to mediate the influence of organizational justice on employee performance. The Head of BPKAD needs to improve individual competence and organizational justice so that it can create job satisfaction which has an impact on improving performance.